Reaction of some rice cultivars to stem rot caused by Sclerotium oryzae Catt. in Manipur - and G.K.N. CHHETRY, JITEN KONTHOUJAM* (Indian Phytopathology, 2007)
Extensive survey covering nearly 12,000hac. of land during 2003-2005Kharif at crop maturity to harvesting revealed that, not a single cultivar / variety was resistant or highly resistant against the disease. Out of thirty four (34) cultivars/varieties screened, only three (3) indigenous local cultivars were moderately resistant against the disease, while the rest were susceptible at different degrees. Soil status and duration of crop had no influence on the type of reaction exhibited by the individual rice cultivars.